Pentingnya Pemberdayaan Masyarakat dalam Pengembangan Usaha Mikro Kecil dan Menengah di Desa Gawu-Gawu Bouso (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study discusses the importance of community empowerment in the development of Micro, Small, and Medium Enterprises in Gawu-gawu Bouso Village. This study aims to identify the current state of community empowerment, the development of micro, small and medium enterprises over the past three years, and the factors that hinder and support micro, small and medium enterprises development in the village. The results are expected to provide input in formulating more effective, sustainable, and locally-based empowerment strategies. The researchers used a qualitative research method. Research Results: (1) Community empowerment in Gawu-Gawu Bouso Village has shown positive efforts through skills training, facilitation of production tools, and mentoring from community empowerment institutions and the village government. However, its implementation has not been optimal because it has not reached all micro, small and medium enterprises actors and has not been carried out routinely and sustainably. (2) micro, small and medium enterprises in the village have experienced quite good development in the last three years, with an increase in the number of business actors and product variations that reflect local potential. However, challenges such as marketing, packaging, and business management are still the main obstacles in increasing competitiveness. (3) Supporting factors for empowerment include support from the village government and community empowerment institutions, training, and cooperation with village- owned enterprises. Meanwhile, inhibiting factors include limited capital, production tools, technological insight, self-confidence of business actors, and low purchasing power of the community.